The Complement Component 5 gene and Age-related Macular Degeneration - Baas, Dominique C. (2009)
OBJECTIVE: To investigate the association between variants in the complement component 5 (C5) gene and age-related macular degeneration (AMD). DESIGN: Separate and combined data from three large AMD case-control studies and a prospective population-based study (The Rotterdam Study). PARTICIPANTS: A total of 2599 AMD cases and 3458 ethnically matched controls. METHODS: Fifteen single nucleotide polymorphisms (SNPs) spanning the C5 gene were initially genotyped in 375 cases and 199 controls from the Netherlands (The AMRO-NL study population). Replication testing of selected SNPs was performed in the Rotterdam Study (NL) and study populations from Southampton, United Kingdom (UK) and New York, United States (US). MAIN OUTCOME MEASURES: Early and late stages of prevalent and incident AMD, graded according to (a modification of) the international grading and classification system of AMD. RESULTS: Significant allelic or genotypic associations between eight C5 SNPs and AMD were found in the AMRO-NL study and this risk appeared independently of CFH Y402H, LOC387715 A69S, age and gender. None of these findings could be confirmed consistently in three replication populations. CONCLUSIONS: Although the complement pathway, including C5, plays a crucial role in AMD, and the C5 protein is present in drusen, no consistent significant associations between C5 SNPs and AMD were found in all studies. The implications for genetic screening of AMD are discussed.